Development of high-throughput genome editing tools towards ethylene production in Cupriavidus species - Vaud, Sophie (2019)
Depletion of natural hydrocarbon resources has catalysed research interest into sustainable routes for the production of bulk chemicals. Cupriavidus necator H16 has been extensively studied for the production of polyhydroxybutyrate (PHB), a biopolymer utilised as an alternative to petroleum-based plastics. However, the strain lacks efficient, fast, and user-friendly strain engineering tools. A single mutant is typically generated via a conjugation/counterselection method, which requires multiple steps and results in a maximum efficiency of 50%, necessitating extensive screening via colony PCR.